Pendidikan Sekolah Sentra dalam Pengembangan Karakter Siswa Islami - Ahmad Arif Fadillah (Publikasi Indonesia, 2022)
This research aims to determine the effect of the application of intermediate techniques in learning Islamic Religious Education on the development of the child's personality. Coaching which is a good time for children can play an important role in shaping their personality. So there must be work from tutoring experts to find the type of learning that suits the development of today's children living in the education department. progress. Sentra is an application designed to change children's moral, mental and scientific knowledge to improve something. The results showed that the instructive experiences that utilize the seven parts of the center are 1) availability, 2) blocks, 3) abilities, 4) difficult tasks, 5) typical materials, 6) body training, and 7) faith and piety, as well as contributing in strengthening the mental, psychomotor, and social communication perspectives of adolescents. Also, the assimilation of these techniques in the PAI educational experience can relate to the student's strict personal setting. The fundamental key to the outcome of using this technique is consistency of action. make critical commitments in fortifying children's mental, psychomotor, and social connections. What's more, the assimilation of these strategies in a developing PAI experience can link students' rigid personal development. The main key to the results of using this strategy is consistency of movement. make a major commitment to fortify the mental, psychomotor, and social communication of young people. Furthermore, the assimilation of these strategies in the PAI educational experience can link students' rigorous personal development. An important aspect of progress using this technique is the determination of movement. Data query is accomplished by plotting the data, isolating it into units, consolidating them, coordinating them into models, choosing what is large and what to dissect, and creating goals that can be communicated to others.